2002
DOI: 10.1300/j013v35n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Women Referred for On-Site Domestic Violence Services in a Managed Care Organization

Abstract: Comprehensive programs in the health care setting can increase identification of victims of domestic abuse. This descriptive report provides a greater understanding of victims of domestic abuse, their presentation in the medical setting, their motivation for accepting referral, and issues which affect their recovery. Links between health care and community resources are necessary for effective intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…This finding is consistent with that of Evanson (2003) regarding the importance of building rapport by healthcare providers in order to be effective advocates for women in violent relationships. McCaw, Bauer, Berman, Mooney, Holmberg, and Hunkeler (2002) reported that women in their study who accepted referrals from healthcare providers had been with their provider for over 15 years. Time constraints due to staffing shortages, budget cuts, and the institutional lack of privacy are barriers to overcome in creating the rapport needed to build trust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that of Evanson (2003) regarding the importance of building rapport by healthcare providers in order to be effective advocates for women in violent relationships. McCaw, Bauer, Berman, Mooney, Holmberg, and Hunkeler (2002) reported that women in their study who accepted referrals from healthcare providers had been with their provider for over 15 years. Time constraints due to staffing shortages, budget cuts, and the institutional lack of privacy are barriers to overcome in creating the rapport needed to build trust.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most of the studies that have been conducted to examine various therapeutic interventions with abused women, have been carried out with groups that had open enrollment (Henderson, 1995;McCaw et al, 2002). In these groups, women never knew who would be there and who would not.…”
Section: Discussionmentioning
confidence: 99%
“…Lowered trust may also be related to women's beliefs about the health care system such as the following: she would be reported to the police, she would be blamed for not leaving, her thinking the nurse or physician will not be able to help, physicians thinking abuse is not a medical problem, and fear of losing her children (Gerbert et al, 1999;Lutenbacher et al, 2003;Mayer, 2000;Yam, 2000). Immigrant women have additional barriers to disclosure including language and fear of deportation, and some share cultural taboos with other minorities against seeking help from strangers or revealing personal family information (McCaw et al 2002;Pinn & Chunko, 1997). A last barrier is that she may have disclosed previously and had health providers ignore the statement or do nothing beyond acknowledge it (Lutenbacher et al, 2003).…”
Section: Ecology Of Disclosurementioning
confidence: 99%
“…Consulting, specifically consultee-centered consultation, involves the consultant helping a consultee with a problem involving a client (Caplan, 1970;Caplan & Caplan, 1993;Knotek & Sandoval, 2003). A literature review revealed consultee-centered consultation programs related to medical and law enforcement professionals working with domestic violence victims involved risk prevention, referral to community resources, and legal intervention (Corcoran & Cawood, 2003;Felson, Ackerman, & Gallagher, 2005;Huisman, Martinez, & Wilson, 2005;Kernic & Bonomi, 2007;McCaw, Bauer, Berman, Mooney, & Holmberg, 2002;Rhodes, Gordon, & Zelman, 1996). Consultees, in the proposed helping paradigm, include law enforcement and emergency room personnel.…”
Section: The Need For a Helping Paradigmmentioning
confidence: 99%